PENDIDIKAN SEKS BAGI ANAK SEKOLAH MINGGU USIA 7-14 TAHUN - Jefri Susanto Manik; Nadia Illsye Tular (Voice of Wesley: Jurnal Ilmiah Musik dan Agama, 2022)
Seeing the number of acts of sexual violence against children which is increasing every year in Indonesia, the church should be aware of the importance of providing sex education to children from an early age. The church as an integral part of society and as the "hand of God" on earth, has a duty, strategic position, and responsibility to provide education through the field of service in the Sunday School category. However, there are still many churches that are silent due to many factors, such as lack of knowledge, lack of human resources, as well as lack of concern. Therefore, this paper will describe a review of sex according to the Bible, a review of the Sunday School according to the Bible, the importance of sex education for Sunday School children, then formulate sex education for Sunday School children. The hope is that the church provides sexual education to its Sunday school children to save God's children from perpetrators of sexual violence. The research method used in this paper is qualitative research with a literature study approach. Through a critical study, the results of this paper are used as the theological basis for practicing sex education for Sunday School children.